2022
DOI: 10.1371/journal.pone.0271001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between research activities and individual factors among Japanese nursing researchers during the COVID-19 pandemic

Abstract: Aim To explore the individual factors (such as gender, division of household labor, childcare and elder care) and their impact on research activities in the Japanese nursing research community during the early stage of the COVID-19 pandemic from April to June in 2020. Design Cross-sectional study. Methods An online survey with a self-reported questionnaire was conducted on Japan Academy of Nursing Science members to explore the impacts of individual factors among Japanese nursing researchers from April to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Previous studies by the JANS project have also shown a relationship between motivation and time spent on research activities (Takeuchi et al, 2022), difficulty in securing sufficient time as a disincentive to research activities (Amano et al, 2021), and other negative environments for research activities and low motivation (Miki et al, 2020). Since the percentage of time spent on research activities among university faculties in Japan has been declining overall, especially in health fields including nursing (MEXT, 2018), it can be inferred that this trend will become stronger with the prolonged COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies by the JANS project have also shown a relationship between motivation and time spent on research activities (Takeuchi et al, 2022), difficulty in securing sufficient time as a disincentive to research activities (Amano et al, 2021), and other negative environments for research activities and low motivation (Miki et al, 2020). Since the percentage of time spent on research activities among university faculties in Japan has been declining overall, especially in health fields including nursing (MEXT, 2018), it can be inferred that this trend will become stronger with the prolonged COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…To date, five papers have used this JANS data: (1) Yoshinaga et al (2021), (2) Amano et al (2021), (3) Kazawa et al (2022), (4) Inoue et al (2022) and (5) Takeuchi et al (2022). Yoshinaga et al (2021) extracted data from the nursing college faculty and found a decrease in time spent on research activities and an increase in time spent on teaching.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation